Role of pharmacists during the COVID‐19 pandemic in China‐Shanghai experiences - Liao, Yun (J Am Coll Clin Pharm, 2020)
The roles and contributions of pharmacists in Shanghai during the coronavirus disease 2019 (COVID‐19) pandemic are described in this report. Five pharmacists have been appointed as members of an expert interdisciplinary health care team tasked with taking care of all adult patients with COVID‐19 in Shanghai in a designated hospital, the Shanghai Public Health Clinical Center (SPHCC). They work with pharmacists at SPHCC, having responsibilities that include drug supplies, dispensing, pharmacy intravenous admixture services (PIVAS), prescription audits, medication reconciliations, pharmacotherapy, therapeutic drug monitoring, and patient education. Due to the pandemic, pharmacy operations in all hospitals are modified to adhere to guidelines for infection risk mitigation and personnel protection. Community pharmacies serve as the public access point to health care and medical supplies, providing services beyond dispensing and medication counselling. The establishment of internet hospitals (telehealth facilities) provide new opportunities for delivering pharmaceutical care and working with health care professionals. Pharmacists also participate in evaluating new treatments and keeping health care teams informed of new findings for potential treatment considerations. In response to the critical need for health care professionals in Wuhan, 68 pharmacists from different parts of the country went there to work with the local pharmacists. Through assuming new roles and adapting existing practice, pharmacists have acquired invaluable experiences for future practice advancement. In order to assume these responsibilities effectively, pharmacists need to be equipped with the necessary skills for meeting the evolving health care challenges.